Caracterização química, atividade antioxidante e antimicrobiana do óleo essencial de Baccharis oreophila Malme - Oliveira, Cledes Terezinha de (2016)
The Baccharis oreophila Malme belongs to the Asteraceae family. In Brazil are reported 120 species of Baccharis, most located in the South and Southeast regions, the latter presents the highest prevalence, especially in the state of São Paulo. Asteraceae is well known for the production of essential oils, which are liquid, volatile and aromatic substances produced by plants specialized for metabolism possess antibacterial, antifungal, and antioxidant properties. Thus, this study aimed, perform chemical and evaluate the antimicrobial and antioxidant activity of essential oil from dried leaves of B. oreophila collected in winter in Piraquara, Paraná. Obtaining essential oil was given by hydrodistillation in Clevenger apparatus, in triplicate, and the analysis was done using a gas chromatograph coupled to mass spectrometry GC / MS. The identification of the components was made based on retention indices calculated from the co-injection of a series of n-alkanes, followed by comparison of their mass spectra with literature. The antimicrobial activity was assessed by disk diffusion method and microdilution. The antioxidant activity was evaluated by the methods DPPH equivalent Trolox, ABTS and FRAP equivalent Trolox equivalent ferrous sulfate. The essential oil showed 0.47% yield. They identified 57 components (89.38%), 1.51% were classified as hydrogenated monoterpenes, oxygenated monoterpenes 15.14%, 34.84% and 37.87% hydrogenated sesquiterpenes sesquiterpenes oxygenates. As the major components were detected kusimono (16.37%), spathulenol (16.12%), the δ-cadinene (5.68%) and bicyclogermacrene (4.09%). The antimicrobial activity of essential oil was performed for the microorganisms Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Candida albicans ATCC 18804 and Candida tropicalis ATCC 13803, the results showed that the essential oil showed activity against S. aureus Inhibitory Concentration minimum (CIM) 1250 g/mL. In the evaluation of antioxidant activity essential oil showed antioxidant potential for the three methods evaluated, with values of 1,468 m.mol.L-1, 7.126 m.mol.L-1 and 45.515 m.mol.L-1 for ABTS, DPPH and FRAP, respectively. These results demonstrate that the essential oil of B. oreophila showed antimicrobial potential against S. aureus and interesting antioxidant activity, especially for the reducing power of iron ion, demonstrating their potential for future industrial applications. It is important to emphasize that were not observed in the literature reports highlighting such biological properties of B. oreophila oil.